2022
DOI: 10.1177/03611981221112092
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Experiment and Characteristics Analysis of Ground Vibrations Induced by Vehicle Loads Moving on an Urban Trunk Road

Abstract: In urban areas, the ground vibrations induced by vehicle loads are becoming an increasingly serious environmental issue, especially in the planning and design of high-tech workshops. In this paper, traffic flow and ground vibrations are simultaneously measured from the vehicles moving on a trunk road in Beijing from 9:30 a.m. to 9:30 p.m. The correlation between traffic volume and ground vibration is calculated to analyze the contribution of different vehicle types and density. The characteristics of ground vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Beben et al [3] observed that the distance between buildings and fences played a vital role in reducing traffic vibration on damaged buildings. Cao et al [4] identified that multi-peak ground vibration in a short time would impact the normal operation of precision instruments in a vehicle during monitoring of vehicle vibration on a trunk road in Beijing.…”
Section: Introductionmentioning
confidence: 99%
“…Beben et al [3] observed that the distance between buildings and fences played a vital role in reducing traffic vibration on damaged buildings. Cao et al [4] identified that multi-peak ground vibration in a short time would impact the normal operation of precision instruments in a vehicle during monitoring of vehicle vibration on a trunk road in Beijing.…”
Section: Introductionmentioning
confidence: 99%